1982
DOI: 10.1093/ajcn/35.3.574
|View full text |Cite
|
Sign up to set email alerts
|

Dietary practices and xerophthalmia among Indonesian children

Abstract: The stated frequency with which 30 Indonesian children with corneal xerophthalmia and age/sex/neighborhood matched controls ordinarily consumed vitamin- and provitamin A-rich foods was compared. Controls were more frequent consumers of eggs (p less than 0.05), fish (p less than 0.05), dark green leafy vegetables (p less than 0.05), carrots (p less than 0.01), and carotene-containing fruits (p less than 0.1). Similar data were collected on 358 children with Bitot's spots and on normal preschool age children in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 14 publications
4
36
0
1
Order By: Relevance
“…For example, in Guatemala, vitamin A is added to sugar [24] in addition to intermittent supplementation programs, together yielding a low rate of VAD determined by serum retinol [25]. Despite the Cochrane reviews limiting maternal, neonatal, and infant vitamin A supplementation in developing countries [26,27], continued emphasis should be placed on vitamin A supplementation programs in Southeast Asia given the clearly documented effects on ocular health and mortality [22,28,29]. …”
Section: Mnds Of Greatest Public Concernmentioning
confidence: 99%
“…For example, in Guatemala, vitamin A is added to sugar [24] in addition to intermittent supplementation programs, together yielding a low rate of VAD determined by serum retinol [25]. Despite the Cochrane reviews limiting maternal, neonatal, and infant vitamin A supplementation in developing countries [26,27], continued emphasis should be placed on vitamin A supplementation programs in Southeast Asia given the clearly documented effects on ocular health and mortality [22,28,29]. …”
Section: Mnds Of Greatest Public Concernmentioning
confidence: 99%
“…There is a large literature linking a low, current intake of vitamin A to xerophthalmia in preschool-aged children (Blankhart, 1967;Pepping et al, 1989Solon et al, 1978Sommer & West, 1996;Tarwotjo et al, 1982). The evidence to date is believed to re¯ect a pattern of chronically low vitamin A intakes.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence to date is believed to re¯ect a pattern of chronically low vitamin A intakes. Yet, beyond a propensity to wean early Tarwotjo et al, 1982) little is known about complementary feeding patterns during early infancy of high-risk children prior to developing clinically evident vitamin A de®ciency (VAD). Secondly, given that younger siblings are at a greatly increased risk of developing xerophthalmia (Katz et al, 1993) and that risk factors tend to cluster within families (Sommer & West, 1996), it is of interest to understand early dietary patterns of prexerophthalmic siblings in order to identify inadequacies of intake and develop more comprehensive dietary counseling strategies for high-risk families and their children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vitamin-A showed a low positive correlation with β-carotene (r = 0.135) and albumin (r = 0.065) but negative with total proteins (r = !0.187) and globulins (r = !0.220). Tarwotjo et al (1982) reported that plasma carotene not necessarily provide a good index of vitamin-A status.…”
Section: Results and Discussion β-Carotene And Vitamin-amentioning
confidence: 99%